Umbilical Arteriovenous Malformation in a Healthy Neonate with Umbilical Hernia - Mariano Marcelo Boglione; Pablo D´Alessandro; Aixa Reusmann; Martín Rubio; José Lipsich; Gustavo Goldsmith (EL-Med-Pub, 2013)
We describe the case of a neonate with an umbilical hernia and persistent wet umbilicus. Examination revealed a pulsatile umbilical cord with palpable thrill. Doppler ultrasound suspected umbilical arteriovenous malformation and contrast-enhanced computed tomography was performed leading to a definitive diagnosis. Surgery was successfully performed on day 27.